1974
DOI: 10.1007/bf00151214
|View full text |Cite
|
Sign up to set email alerts
|

The third harmonic of type III solar radio bursts

Abstract: Two examples of pairs of 'J-shaped' type III bursts with 2: 3 frequency ratio are given. It is suggested that these could be the second and the third harmonics of undetected fundamental radiation. The 80 MHz heliograph source of the third harmonic showed an apparent brightness temperature of 109.6 K, while the order of 1016K seems to be required theoretically. This may imply that the apparent radio source was composed of many unresolved small sources of much higher brightness temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

1974
1974
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 1 publication
1
13
0
Order By: Relevance
“…According to some reported observations (Reiner et al 1992;Zlotnik et al 1998), the 3H component is weaker than the 2H radiation. On the other hand, other observations report more intense 3H emission than the 2H component (Takakura & Yousef 1974). This conflicting relative difference in the radiation intensity has been the source of some controversy (Zlotnik 1978).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to some reported observations (Reiner et al 1992;Zlotnik et al 1998), the 3H component is weaker than the 2H radiation. On the other hand, other observations report more intense 3H emission than the 2H component (Takakura & Yousef 1974). This conflicting relative difference in the radiation intensity has been the source of some controversy (Zlotnik 1978).…”
Section: Resultsmentioning
confidence: 99%
“…The radiation emission at higher harmonics of plasma frequency has been observed in solar and interplanetary environment (Kliem et al 1992;Zlotnik et al 1998;Takakura & Yousef 1974;Benz 1973;Cairns 1986). However, the issue of whether such a phenomenon is even possible in plasmas has not been resolved.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observations have also shown that the third harmonic emission is usually very weak. Here one should note that there are several observed cases of third harmonics in solar radio bursts [ Benz , ; Takakura and Yousef , ; Bakunin et al , ; Kliem et al ].…”
Section: Discussionmentioning
confidence: 99%
“…Another modification of plasma emission, which is not discussed here, involves including a third harmonic (Takakura and Yousef, 1974;Zlotnik et al, 1998;Yoon et al, 2002;Fomichev et al, 2013).…”
Section: Fine Structuresmentioning
confidence: 99%